SUPPORTING SOLVING WORD PROBLEMS INVOLVING RATIO THROUGH THE BAR MODEL - Siti Nurain Said; Khairul Amilin Tengah (Jurnal Infinity, 2021)
The weak ability for students to correctly attempt word problem question in mathematics have pushed researcher to study multiple approach in attempting such questions. This study examined the effectiveness of the Bar Model as a problem solving heuristic in improving Year 8 students’ performance in solving word problems involving ratio. A total of thirty-three Year 8 students from a secondary school in Brunei Darussalam were involved in the study. Data were collected through pre-test and post-test. Paired sample t-test on the mean score of pre-test and post-test showed a significant improvement in the students’ mean marks (t = - 8.079).  The results also revealed that the Bar Model is capable of helping students of all abilities particularly the weaker students. Hence for this study, the Bar Model successfully enhanced the lower secondary students’ performance in solving word problems involving ratio, particularThy when presented as public examination questions.